Future and Current Research Directions of FinTech: A Bibliometric Analysis - Asif, Muhammad; Sarwar, Farhan; Lodhi, Rab Nawaz (Audit and Accounting Review, 2023)
The current study aims to perform a bibliometric analysis of Fintech. For this purpose, 1,135 articles indexed on Scopus from 2002-2021 were reviewed that focused on Fintech and the banking sector. The study identified and searched "Fintech" OR “FinTech” OR Financial Technology” OR “financial technology” keyword within the title indexed on Scopus. In the second step, MS Excel and VOS viewer were used to provide visualization network and descriptive analysis of co-citation, bibliographic coupling, citation, co-occurrence of keywords and co-authorship analysis. The study found that 2021 was the leading year with 389 articles, which accounted for 34.3% of total publications, in which China was identified as the most productive country having 142 publications, accounting for 12.5% of total the publications. The current study’s findings can help the future researchers and practitioners in the banking sector to take informed decisions regarding Fintech research, which can equally contribute to the advancement of the present knowledge and understanding of Fintech in the banking industry.